2016
DOI: 10.5897/ajps2016.1410
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salicylic acid (SA) seeds soaking on the NaCl salt stress induced changes in soluble sugar and protein accumulation in organs of two genotypes of okra plants

Abstract: Salt stress is a major challenge in agricultural system. In this study, okra seeds of two genotypes (47-7 and LD 88) were presoaked with 10 -2 , 10 -4, and 10 -6 mM salicylic acid and control in distilled water, then the soil was treated with 0, 50, 100, 150 and 200 mM NaCl. The experiment was conducted to study the effect on osmoregulating solutes such as proline, salt stress protein (glycine betaine and proline betaine) and soluble sugars (glucose and fructose). Results showed that proline content increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Exogenous application of SA has been reported to mitigate the adverse effect of salinity on maize growth by increasing production of sugars (Fahad and Bano, 2012) and proline (Hussein et al., 2007). The contribution of proline but not soluble sugars (Esan and Olaiya, 2016) and of proline and Na + but not K + in osmoregulation of okra and maize, respectively under salinity stress has been reported by Cicek and Cakirlar (2002). The limited alterations in protein and phenolics contents of maize leaves in response to hybrid, salinity and SA regime point to limited genotypic variability in these two components and suggests that neither protein nor phenolics can be considered as markers for salt injury/resistance in the two used maize hybrids.…”
Section: Discussionmentioning
confidence: 69%
“…Exogenous application of SA has been reported to mitigate the adverse effect of salinity on maize growth by increasing production of sugars (Fahad and Bano, 2012) and proline (Hussein et al., 2007). The contribution of proline but not soluble sugars (Esan and Olaiya, 2016) and of proline and Na + but not K + in osmoregulation of okra and maize, respectively under salinity stress has been reported by Cicek and Cakirlar (2002). The limited alterations in protein and phenolics contents of maize leaves in response to hybrid, salinity and SA regime point to limited genotypic variability in these two components and suggests that neither protein nor phenolics can be considered as markers for salt injury/resistance in the two used maize hybrids.…”
Section: Discussionmentioning
confidence: 69%
“…In this study, Guang Hong 3 accumulated more proline and soluble protein than the Huang Huazhan variety. It was previously claimed that high concentrations of proline enhance plant tolerance to NaCl stress by increasing the osmoregulatory capacity of plants and reducing cell damage by ROS [37,38]. Proline accumulation is a criterion for determining plant tolerance to salt stress [39].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies indicate the ability of exogenous application of SA under saline conditions to increase the accu-International Journal of Food Science and Agriculture mulation of osmolytes, enhance antioxidant protection, and maintain optimum Na + /K + ratio, which is suggested as potential mechanisms of salt tolerance in plants [11][12]. Our previous works indicated that SA minimizes the negative effects of salt stress by improving accumulation of compatible solutes, and increasing antioxidant activity [13][14]. The aim of this study was to investigate the impact of salicylic acid on some key biochemical and physiological parameters in salt-stressed okra.…”
Section: •−mentioning
confidence: 99%